PERAN KEPALA SEKOLAH DALAM MEMBENTUK SISWA MENJADI GENERASI ENTREPRENEUR DI SMK NUSANTARA MANDIRI KOTA BONTANG - Halimah, Siti; Tahir, M; Asiah, Siti Nor (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2023)
The rapid development in the industrial era has led individuals to acquire skills and an entrepreneurial spirit. Vocational High Schools (SMK) are expected to be one of the educational institutions that contribute significantly to providing solutions. The school principal is required to constantly take relevant and aligned steps in response to these conditions. Therefore, this research aims to determine the role of the school principal in shaping students into entrepreneurial generations at SMK Nusantara Mandiri Bontang. This study utilizes a qualitative method with data collection techniques such as observation, documentation, and interviews. The research findings indicate that the school principal plays multiple roles, including educator, manager, administrator, supervisor, leader, innovator, and motivator. However, there are several obstacles, such as lack of student motivation and creativity, inadequate parental support, difficulties in organizing and being accountable for activities, lack of student cooperation, student unresponsiveness to learning, and student apprenticeship issues. To overcome these obstacles, the solutions include fostering an entrepreneurial spirit through a holistic approach, involving parents and industry speakers, improving information management efficiency, emphasizing industrial work culture, enhancing student discipline through parental involvement, taking innovative steps in education, and creating a conducive environment for the development of students' skills and motivation in the world of works.